BACK PAIN SYNDROME: MODERN APPROACHES TO THERAPY - N. A. Shostak; A. A. Klimenko (Klinicist)
Objective: to describe management tactics in patients with back pain syndrome and to give recommendations for the choice of non-drug and drug treatments (with main drug groups) and the duration of a treatment cycle. Materials and methods. The paper considers the basic mechanisms and causes of back pain syndromes (dorsalgias). It introduces the concept “dorsopathy” that characterizes the appearance of nonvisceral pain syndrome in the extremities and trunk, which is caused by degenerative processes in the vertebral motion segment. The authors provide a description of spondyloarthrosis, one of the main degenerative diseases of the spine, and give current principles of treatment for the major symptoms of the disease. Results. The main goal of treatment in patients with back pain is to relieve pain syndrome. Selective nonsteroidal anti-inflammatory drugs are the medicaments of choice. Conclusion. This paper covers current approaches to managing patients with spondyloarthrosis and gives recommendations regarding the treatment of the major disease manifestation – pain syndrome.